La ley humana en la escolástica, 1526-1617 = The Human Law in Scholasticism, 1526-1617 - Contreras Aguirre, Sebastián Antonio (Cauriensia, 2024)
The scholastics of the sixteenth and seventeenth centuries developed a general theory of human law based on a constant dialogue with Saint Thomas. Among all of them, this paper focuses only on Francisco de Vitoria, Domingo de Soto, Luis de León, and Francisco Suárez, and only on the way they deal with the issue of the definition, effect, and derived character of human law. Vitoria almost exclusively repeats Aquinas. Soto reasons more freely, although he never steps outside the framework of Thomistic theses. León does go beyond this framework, which allows him to offer a truly original reading of those theses. For his part, Suárez reinterprets Aquinas’s teaching and even corrects it when he considers it necessary.